2017
DOI: 10.2514/1.g002181
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Ballistic Soft Landing in Binary Asteroids

Abstract: Remote sensing instrumentation on-board missions to asteroids is paramount to address many of the fundamental questions in modern planetary science. Yet, in-situ surface measurements provide the "ground-truth" necessary to validate and enhance the science return of these missions. Nevertheless, due to the dynamical uncertainties associated with the environment near these objects, most missions spend long periods of times stationed afar. Small landers can be used much more daringly, however, and thus have alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Along the same line of studies, Ferrari and Lavagna performed a trajectory design study and Monte Carlo simulations against uncertainties for MASCOT-2 [14]. In a more recent study, Ç elik and Sánchez proposed a new technique in CR3BP to search opportunities for ballistic soft landing in binary asteroids [15]. This technique defines a landing in local vertical and utilizes a bisection search algorithm to find minimum energy trajectories in backwards propagation from the surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along the same line of studies, Ferrari and Lavagna performed a trajectory design study and Monte Carlo simulations against uncertainties for MASCOT-2 [14]. In a more recent study, Ç elik and Sánchez proposed a new technique in CR3BP to search opportunities for ballistic soft landing in binary asteroids [15]. This technique defines a landing in local vertical and utilizes a bisection search algorithm to find minimum energy trajectories in backwards propagation from the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Ç elik and Sánchez (2017) previously showed that landing trajectories onto larger companions of binaries (thereafter called as the primaries) entail higher energy landing trajectories, which; on the one hand may put the payload on the lander at risk due to the higher touchdown velocities, and on the other hand, do not guarantee that the lander will remain in the surface of the primary, unless very low coefficient of restitution can be ensured [15]. Hence, this paper focuses only on landing in the secondary, which was previously shown to potentially enable ballistic soft landing [15]. The paper particularly addresses the reliability aspects of the deployment operations under realistic uncertainties and errors in navigation and deployment systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two fields of study emerge which are of interest: that of the dynamics of landing and that of the interaction with the soil during impact. Since the 1960s, multi-legged landing systems are considered the state of the art [10] for low-velocity impact during powered descent, while ballistic landing systems have been proposed as well [11]. The reliability of landing systems is critical to the success of the mission [12], both structurally [13,14] as well as functionally [9].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the effect of the soil itself is generally nontrivial to model [17][18][19][20]; it can be simulated using numerical methods [17] or experimentally. The physics of impact and energy dissipation during collisions and landing have been studied from a structural point of view [21][22][23], from a dynamics perspective [1,2,10,16,[23][24][25], and as a mission-planning problem [11,26].…”
Section: Introductionmentioning
confidence: 99%